Rediscovering Wen Tingyun : a historical key to a poetic labyrinth - Mou, Huaichuan, 1946- (SUNY series in Chinese philosophy and culture., 2004)
"In this book, Huaichuan Mou takes a fresh look at the life, times, and work of Wen Tingyun, the great poet of the late Tang dynasty in China, whose reputation has been overshadowed by notoriety and misunderstanding for more than a thousand years. In probing the political intricacies of the major events of Wen's life and the complex contexts in which these events took place, Mou presents a historical key to Wen's artistic labyrinth, unraveling many of Wen's poetic puzzles and rediscovering a historical past that vividly represents his unyielding pursuit of ideal government and true love. This reconstruction of the poet's life results in a new understanding not only of his literary work but also of late Tang history as well. Translations and close readings of a number of poems and prose essays are included."--Jacket